PENENTUAN TINGKAT RISIKO PADA PROSES PRODUKSI GARAM TRADISIONAL DI DESA IE LEUBEU KABUPATEN PIDIE - Pamungkas, Iing; Irawan, Heri Tri; Arkanullah, Lian; Dirhamsyah, Muhammad; Iqbal, Mohd (Jurnal Optimalisasi, 2019)
The community's conventional salt production business is one of the economic drivers of the community. In addition to being able to provide a lot of jobs for people in Indonesia's coastal areas, the people's salt production business is also seen as a way to reduce poverty. Pidie Regency, which is included in the Province of Aceh, is one area that has a wide coastline and can be utilized as a salt farmer business. Pidie is an area that has a salt production business with a total production of 449.05 tons/month. The problem faced in the traditional salt processing business in Pidie District is the unknown level of risk that exists in each salt production process. The purpose of this study is to determine the level of risk in the traditional salt production process using failure mode and effect analysis (FMEA) and probability impact matrix (PIM) in the Saho Adab people's salt business group in Keude Ie Leubeu Village, Kembang Tanjong District, Pidie District. FMEA is a form of qualitative analysis that assesses the severity , occurrence and detection on each activity and then given a value on a predetermined scale. Whereas risk assessment using PIM only assesses the severity and occurrence. Based on the analysis of failure and effect modes, the salt production process has a high level of risk, namely the packaging process with an RPN value (risk priority number) 75, the salt water storage process with an RPN value of 48, the drying process with an RPN value of 45 and the level of the soil process with an RPN 45. While the results of the matrix impact probability obtained by the salt production process that has a high level of risk, namely the process of storing salt with a value of 5, the packaging process with a value of 4, the process of leveling sand with a value of 3,5 and the process of salt water filtration with sand filtration media containing NaCl with a value of 3,5.